Cement-in-cement femoral revisions using a specially designed polished short revision stem; 24 consecutive stems followed for five to seven years. Issue 5 (September 2014) - te Stroet, Martijn A.J.; Moret-Wever, Sander G.; de Kam, Daniël C.J.; Gardeniers, Jean W.M.; Schreurs, B. Willem
Femoral cement-in-cement revisions are attractive if the cement bone mantle is well fixed. However, most available cemented stems are too long to fit in the existing cement mantle. We evaluated the medium-term outcomes of the 125 mm short tapered polished stem (Exeter Short Revision Stem (SRS)) with a 44 mm offset specifically designed to facilitate cement-in-cement revisions of hip arthroplasties. The Exeter SRS was clinically and radiographically evaluated in 24 consecutive femoral cement-in-cement revisions (11 men, 13 women) between July 2005 and February 2008 after a mean follow-up of six years (5-7). The mean age at operation was 67 years (54-83). No hip was lost to follow-up, but two patients (two hips) died. None of the deaths were related to the surgery. Kaplan Meier survival analysis was performed. Four femoral components (17%) were removed for septic loosening after a mean of 2.4 years (0.8-4.9). Three of these hips were revised again in a two-stage revision, and one was converted to a permanent excision arthroplasty. The probability of survival with re-revision for any reason was 82% (95% CI: 58-93) and survivorship with aseptic loosening as the endpoint was 100% at six years. There were no additional radiological failures. The Exeter Short Revision Stem is a valuable option for simplifying cement-in-cement revisions. Despite the short stem length, at mid-term there were no signs of instability or aseptic loosening.